Controllability and reconstructability of a system described by the N-D Roesser model - Kurek, Jerzy E. (Zielona Góra: Uniwersytet Zielonogórski)
The controllability and reconstructability (global) of the system described by a digital N-D Roesser model are defined. Then, necessary and sufficient conditions for system controllability and reconstructability are given. The conditions constitute a generalization of the corresponding conditions for 1-D systems.
Keywords: N-D systems; Roesser model; controllability; reconstructability